Construção e aplicação de um jogo de tabuleiro para o ensino de Física - Favaretto, Danilo Vieira (2017)
The main objective of this work was the elaboration and application of a board game involving physical concepts related to the daily life of the students. The research here points out the importance of using ludic activities to improve students' learning and the exploration of the ability of argumentation, which would not usually be attempt in a traditional classroom. The elaborated product was applied in two classes of the 3rd year of the Secondary School of a private school in the city of Sorocaba. The proposed activity promoted the discussion of physical concepts, associated with group work. It was observed that the interaction between the students and the dialogue were frequent in the classroom when using this methodology, which provided an increase in the interest of the students to learning Physics. Besides that, the more frequent dialogue improved the student-student and student-teacher relations. It is important to emphasize the importance of the interaction between the students in the discussions of the physical concepts and in the construction of the relations between these concepts and their daily activities. In addition to the greater interest of the students in the discipline of Physics, it was possible to observe the development of a critical posture, which has favored the learning in the classroom.